Functional design principles, patterns, and practices - Martin, Robert C. (Addison-Wesley, 2021)
A Practical Guide to Better, Cleaner Code with Functional Programming. In Functional Design, renowned software engineer Robert C. Martin ("Uncle Bob") explains how and why to use functional programming to build better systems for real customers. Martin compares conventional object-oriented coding structures in Java to those enabled by functional languages, identifies the best roles for each, and shows how to build better systems by judiciously using them in context. Martin's approach is pragmatic, minimizing theory in favor of "in the-trenches" problem-solving. Through accessible examples, working developers will discover how the easy-to-learn, semantically rich Clojure language can help them improve code cleanliness, design, discipline, and outcomes. Martin examines well-known SOLID principles and Gang of Four Design Patterns from a functional perspective, revealing why patterns remain extremely valuable to functional programmers, and how to use them to achieve superior results.
Includes index
Keywords: Functional programming (Computer science); Programmation fonctionnelle